2013
DOI: 10.2166/wst.2013.765
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen and carbon dynamics beneath on-site wastewater treatment systems in Pitt County, North Carolina

Abstract: On-site wastewater treatment systems (OWS) are a potentially significant non-point source of nutrients to groundwater and surface waters, and are extensively used in coastal North Carolina. The goal of this study was to determine the treatment efficiency of four OWS in reducing total dissolved nitrogen (TDN) and dissolved organic carbon (DOC) concentrations before discharge to groundwater and/or adjacent surface water. Piezometers were installed for groundwater sample collection and nutrient analysis at four s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 0 publications
5
19
0
Order By: Relevance
“…FIB data were log transformed and a Pearson Correlation test was used to determine if there were significant correlations between the different FIB concentrations, and between FIB concentrations and SC. Correlations between FIB and SC were performed because SC is often elevated in fresh groundwater influenced by effluent [7,25,26].…”
Section: Spatial Distribution Of Fecal Indicatorsmentioning
confidence: 99%
“…FIB data were log transformed and a Pearson Correlation test was used to determine if there were significant correlations between the different FIB concentrations, and between FIB concentrations and SC. Correlations between FIB and SC were performed because SC is often elevated in fresh groundwater influenced by effluent [7,25,26].…”
Section: Spatial Distribution Of Fecal Indicatorsmentioning
confidence: 99%
“…Groundwater and septic effluent TDN concentrations were lowest in July 2013 (27.2 and 41.7 mg L −1 , respectively) and highest in March 2014 (64.8 and 144.7 mg L −1 , respectively) (Figure A). The school operates on a traditional school calendar (late August to early June), thus the lower concentrations of TDN in July could be associated with relatively low flows because of the summer break. The lower concentrations of TDN in groundwater in July may also have been related to an abnormally wet period when rainfall exceeded the long term average by 100%, potentially diluting groundwater TDN concentrations .…”
Section: Resultsmentioning
confidence: 99%
“…O'Driscoll et al reported that during periods of increased precipitation and recharge, the hydraulic gradient near an OSW increased, and thus transport of nitrogen toward the estuary increased. Other studies have shown that when the separation distance between OSW and groundwater decreases, treatment efficiency of wastewater phosphorus, bacteria, carbon, and pharmaceuticals decreases. Prior studies have shown that groundwater levels in coastal North Carolina respond quickly to precipitation events because of the relatively shallow depths to groundwater, and high permeability rates of the sandy soil .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations